Sexual partnership age pairings and risk of HIV acquisition in rural South Africa - Akullian, Adam; Bärnighausen, Till (AIDS <London>, 2017)
OBJECTIVE: To quantify the contribution of specific sexual partner age groups to the risk of HIV acquisition in men and women in a hyperendemic region of South Africa. DESIGN: We conducted a population-based cohort study among women (15-49 years of age) and men (15-55 years of age) between 2004 and 2015 in KwaZulu-Natal, South Africa. METHODS: Generalized additive models were used to estimate smoothed HIV incidence rates across partnership age pairings in men and women. Cox proportional hazards regression was used to estimate the relative risk of HIV acquisition by partner age group. RESULTS: A total of 882 HIV seroconversions were observed in 15935 person-years for women, incidence rate=5.5 per 100 person-years [95% confidence interval (CI), 5.2-5.9] and 270 HIV seroconversions were observed in 9372 person-years for men, incidence rate=2.9 per 100 person-years (95% CI, 2.6-3.2). HIV incidence was highest among 15-24-year-old women reporting partnerships with 30-34-year-old men, incidence rate=9.7 per 100 person-years (95% CI, 7.2-13.1). Risk of HIV acquisition in women was associated with male partners aged 25-29 years (adjusted hazard ratio; aHR=1.44, 95% CI, 1.02-2.04) and 30-34 years (aHR=1.50, 95% CI, 1.08-2.09) relative to male partners aged 35 and above. Risk of HIV acquisition in men was associated with 25-29-year-old (aHR=1.72, 95% CI, 1.02-2.90) and 30-34-year-old women (aHR=2.12, 95% CI, 1.03-4.39) compared to partnerships with women aged 15-19 years. CONCLUSION: Age of sexual partner is a major risk factor for HIV acquisition in both men and women, independent of one's own age. Partner age pairings play a critical role in driving the cycle of HIV transmission.
Gesehen am 12.04.2018